Antidepressant treatment outcomes in family medicine - Subhija Prasko; Nurka Pranjić; Larisa Gavran; Alma Alić; Ibrahim Gledo; Enisa Ramić; Emina Spahić; Erna Prasko; Irma Ramić (Medicinski glasnik, 2019)
Aim: To determine the prevalence of depressive episodes and recurrent depressive disorders despite of the length of therapy and type of antidepressants. Methods: The study was conducted among 508 patients aged 19-65 years who were treated for depression for at least 3 months (mild and moderate episodes were controlled and the effects of treatment monitored by family physicians, while severe episodes were controlled by a psychiatrist) during 2013- 2015 in Zenica-Doboj Canton using the Hamilton Depression Rating Scale (HDRS). Results: The average age of the patients was 48.98±11.585 years. Depressive disorder was most commonly represented in patients with high-level education, 22%, more frequently in non-productive workers (non-productive vs. manufacturing 58%:35%). A significant number of patients who were treated for depression were unemployed (57%). All respondents were suffering from the most serious episode of depression with an average depression rate at the Hamilton scale 18.49±8.603, with a very serious depression level of 32%, severe 17%, moderate 21%, and mild 20%. Most patients were treated with paroxetine, 27%, fluoxetine 22% and sertraline 17%. Efficacy of depression treatment with different types of selective serotonin reuptake inhibitors antidepressants (SSRIs) was not significantly different (p=0.502). Conclusion: Success of the treatment with the absence of symptoms of depression was achieved in 10% and the maintenance of depressive episodes occurred in 90% of cases. Adverse reactions with the most commonly prescribed SSRI in our country should be important in creating procedures and strategies for the future treatment of depression in family medicine.
Keywords: depressive episodes; effects of medications; antidepressant side effects; general practitioners; recurrent depressive disorders